Hbr's 10 must reads on public speaking and presenting - Review, Harvard Business (Gildan Audio, 2020)
Command the room-whether you're speaking to an audience of one or to hundreds.We've combed through hundreds of Harvard Business Review articles and selected the ten most important ones to help you speak confidently in front of a group and connect with audiences of any size.This book will inspire you to: feel more confident when it's your turn to present; understand how to persuade, motivate, and change minds; frame your message so people really listen; gain your audience's trust by being more authentic; use visuals and data more effectively; learn to be more charismatic; and infuse your day-to-day communication with storytelling.